Determinan Efektivitas Sistem Pengendalian Internal Perusahaan - Ratna Andita Dewi (Akuntabilitas, 2016)
This research is to examine empirically the influence of role, professionalism, working experiences and internal auditor’s IT knowledge on enterprise’s internal control system effectiveness based on purposive sampling method, this research used a sample of 71 respondents who work as internal auditors at some private enterprises in DKI Jakarta region. data was analyzed multiple regression analysis with spss 22 processing. The result of this research indicates that professionalism, working experiences and internal auditor’s IT knowledge have an influence on enterprise’s internal control system effectiveness while the role of internal auditor does not have an influence on enterprise’s internal control system effectiveness.